Analisis Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) di Indonesia - Yurnalisdel Yurnalisdel (Syntax Corporation Indonesia, 2023)
Hazardous and Toxic Materials are substances, energy, and/or other components which due to their nature, concentration and/or amount, either directly or indirectly, can pollute and/or damage the environment, endanger the environment, health and survival of humans and living thing.. Hazardous and toxic waste materials are. The management of this hazardous and toxic waste is very crucial given the impact it will have on human health. So this study aims to analyze the management of Hazardous and Toxic Materials (B3) waste in Indonesia. This study uses a literature review method with a qualitative approach. This literature review is by searching for data, selecting the necessary data, analyzing it, and making conclusions from the results of data analysis. The results obtained are that the management of hazardous and toxic waste in the stages of collection, separation, storage, transportation and processing of waste must be carried out properly and safely.